Parfit’s non-identity problem - Khodadadi, Hossein (Journal of the Belarusian State University. Philosophy and Psychology, 2024)
One of the longstanding issues that haunted the minds of many philosophers is our responsibility toward future generations. D. Parfit put forward one of the philosophical arguments that real people cannot be held accountable for the harm caused by their actions. Future people, as long as they have a decent life, cannot complain about a possible catastrophic situation created by the society that lives now, because subject-subject debt relationship can only exist between certain and existing people. D. Parfit’s counterintuitive idea has been challenged by philosophers. In recent literature A. Wrigley sets out to provide a solution to the problem of nonidentity drawing on the D. Lewis’s metaphysics of modality. It is reasoned why the proposal of A. Wrigley cannot solve the problems about non-existent people advanced by D. Parfit.
Keywords: D. Parfit; D. Lewis; modality; identity; non-identity